Utilization of waste heat from cement plant to generate hydrogen and blend it with natural gas - Ozturk, Merve; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this paper, a waste heat recovery system for a cement plant is developed and analyzed with the softwares of Engineering Equation Solver (EES) and Aspen Plus. This system is novel in a way that hydrogen is uniquely produced from waste heat obtained from the cement slag and blended with natural gas for domestic use. The presented system has a steam Rankine cycle combined with an organic Rankine cycle, an alkaline electrolyzer unit, oxygen and hydrogen storage tanks, a blending unit, and a combustor. Moreover, multiple useful outputs are obtained, such as power, hydrogen, and natural gas, as well as hydrogen blend. The power obtained from the organic Rankine cycle becomes the highest when the organic fluid R600a is used as a working fluid. The power generated from turbines is fed to the grid externally and the cement plant for internal use. Also, some power is utilized to produce hydrogen via an alkaline electrolyzer which has an efficiency of 62.94%. With the change of the percentage of hydrogen in the blend from 0% to 50%, the annual consumption of natural gas reduces from 48.261 billion m(3) to 37.086 billion m(3). Furthermore, the overall exergy and energy efficiencies for the plant are found at 55% and 22%, respectively. The carbon dioxide emissions in the released exhaust gas reduce from 34% to 28% when the same volumetric flow rates of the blend and oxygen gas are fed to the reactor. NO and NO2 emissions increase from 4.06 g/day to 7.45 g/day, and from 0.02 g/day to 0.09 g/day when the hydrogen content is increased from 5% to 20%. Moreover, carbon monoxide emissions decrease from 0.05 g/day to 0.02 g/day, accordingly. As a result, both combustion energy and exergy efficiencies increase with the addition of hydrogen. Furthermore, CO and CO2 emissions decrease with the hydrogen content increases. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Natural gas; Waste heat recovery; Emission; Energy; Exergy; ENERGY CARRIER; RECOVERY; STORAGE; Chemistry; Electrochemistry; Energy & Fuels